Рентгенівське випромінювання, викликане імпульсною лазерною дією на опалові матриці - Belyanin, A. F.; Borisov, V. V.; Popov, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2018)
The paper presents the structure and preparation conditions of opal matrices (ordered 3D-lattice packing of X-ray amorphous SiO2 spheres with a diameter of ≈250 nm), as well as experimental data on nonlinear optical effects in opal matrices with pulsed laser excitation at wavelengths: 1040 nm, 510 nm in conjunction with 578 nm, and 366 nm. The authors investigate the energy spectra of X-ray radiation induced in the samples by laser irradiation.